Pelatihan Pengelolaan Sampah Organik di Desa Jurumapin Berbasis Kompos Limbah Rumah Tangga - Heri Kusnayadi; Siti Nurwahidah; Syahdi Mastar; Nila Wijayanti (LPPM Universitas Trunojoyo Madura, 2021)
The aim of Samawa University, one of which is to provide organic compost training and practice of manufacturing organic fertilizer in the village of Jurumapin, Buer district West Nusa Tenggara. Compost is an organic fertilizer derived from the remains of plants and animal droppings that have been through a decomposition or weathering process. Compost fertilizer is the main ingredient in cow dung. The advantage of this post is green, which may supplement the farmers' income and can increase soil fertility by repairing soil physically damaged by overuse of inorganic fertilizer. The village of Jurumapin was mainly farmers and ranchers. The waste produced by the people's domesticated animals has not been fully processed for fertilizer. Prolonged use of chemical fertilizers can cause physical damage to the soil, as well as the cost of purchasing fertilizer is prohibitive. The implementation of this MTC programme will be by educating them on how organic compost with basic cow dung. The development of organic fertilizer has been carried out with participants who are members of the caduna youth of the mosque of the Jurumapin village. It is hoped that organic compost products could be applied to plants to reduce the use of chemical fertilizer